A Review of Antidiabetic Potential of Indonesian Medicinal Plants on Streptozotocin (STZ)-Induced Rats - Anjabtsawa, Daffa; Febriyanti, Raden Maya; Diantini, Ajeng (Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, 2024)
Diabetes mellitus represents a chronic pathological state affecting a substantial portion of the global population, characterized by elevated levels of blood glucose. The International Diabetes Federation (IDF) documented in 2022 an estimated 537 million individuals aged 20-79 afflicted with this condition. Indonesia is home to various medicinal plants used for centuries to treat various ailments, including diabetes. Some of these plants have been found to have antidiabetic properties and are currently being studied for their potential use in treating diabetes. This review integrates the potential of indigenous Indonesian medicinal plants as antidiabetic agents. Twenty-two herbal species native to Indonesia were examined in diabetic-rat models, revealing promising efficacy as alternatives to conventional antihyperglycemic therapies. These medicinal plants' bioactive constituents, including flavonoids, alkaloids, phenolics, tannins, saponins, steroids, triterpenoids, and glycosides, are hypothesized to modulate glucose metabolism. Data acquisition encompassed scholarly databases such as PubMed, Scopus, Cochrane, Google Scholar, ScienceDirect, and EBSCO, spanning literature published between 2017 and 2023. The investigation underscores the notable reduction in blood glucose levels observed in rats administered doses ranging from 100 to 800 mg/kg body weight (BW). Furthermore, the antihyperglycemic evaluation in rats involved dosing at 40-65 mg/kg BW, eliciting a sustained hyperglycemic state.